SKILLS AND ATTITUDES TOWARDS USING AI BASED CHATBOTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The results of a survey conducted in 2023 on skills and attitudes towards the use of Artificial Intelligence are presented. The study included employees working in the public administration in the Republic of Bulgaria and students from the Cybersecurity specialty. The aim was to find out to what extent and area of interest the two target groups work with or are willing to start using ChatGPT or similar chatbots. The questions asked in chatbots, as well as the listed by both groups advantages and disadvantages can be used as one of the indicators when creating the teaching materials for school or university courses, as well as for the updating of already ongoing training programs.